Putusan Pengadilan Agama Badung Nomor 0166/Pdt.G/2017/PA. Bdg Tentang Cerai Gugat Karena Salah Satu Pihak Berbeda Agama - I Putu Wina Wirawan; I NYOMAN PUTU BUDIARTHA; NI MADE PUSPASUTARI UJIANTI (Jurnal Preferensi Hukum, 2020)
Marriage is a sacred bond because in that marriage bond there are not only physical and mental bonds but also spiritual bonds based on God Almighty. A lawsuit divorce is the breaking of the husband and wife ties, in which case the wife is the one who filed a divorce suit against the husband. This study aims to determine why religious differences can be used as an excuse for a legal divorce in the Badung religious court and to find out the judges' considerations in cases at the Badung religious court. The type of research used in this research is Empirical Legal Research, which is taken based on facts that occur in the field, which are obtained through explanations from informants and studied with real legal attitudes or in accordance with life in society. The result of this research is that religious differences are used as the reason for a legal divorce in the Badung religious court in fact the marriage law and its implementing regulations do not regulate religious conversion (murtad) as the reason for breaking up a marriage because the State of Indonesia adheres to the principle of religious freedom. However, the KHI in Article 116 letter (k) states one of the reasons for divorce, namely when one of the parties leaves the religion (murtad). 2) The considerations of the panel of judges in a sue divorce case at the Badung religious court already have strong considerations and reasons to be used as a basis for making a decision, such as in the case decision Number 0166 / Pdt.G / 2017 / PA.Bdg. So it can be concluded that Divorce is only said to be valid after a court decision has permanent legal force, and the Panel of Judges in adjudicating a proposed divorce case must know clearly the facts that cause religious conversion.